“Desarrollo de un sistema web para el control y gestión administrativa del gimnasio "Kevin Gym" del cantón La Maná”. - Morejón Oña, Darwin Alexis (2023)
Information systems are considered one of the relevant components in all areas as agriculture, business, health, education, management, and administration, so information systems offer great opportunities for success for companies with their contribution can improve processes and decision-making through web application development. The present research has as its objective to develop a web system for the administrative management control of Kevin GYM for the construction is used the programming language PHP and a database Mysql with the agile methodology Scrum that allows obtaining a software product in short periods. To meet this objective, we applied the literature review methods that allowed us to identify scientific publications related to the research topic obtained from a scientific database. From these publications, we made a thorough analysis of software development processes, in which we found research that allowed us to identify the application of tools for these systems. As a result, the development of a web system for the needs of the user administrator to verify the system function was subjected to black-and-white box testing. To conclude, the Scrum methodology is a working model that efficiently supports the development process in short periods where deliverables and tools are obtained in an agile way as user stories and task lists and incorporate the product stakeholder in the process.